Effect of elasto-plastic material behaviour on determination of residual stress profiles using the hole drilling method. (November 2016) - Chupakhin, Sergey; Kashaev, Nikolai; Huber, Norbert
The hole drilling method is a well-known technique for the determination of non-uniform residual stress profiles by measuring relaxation distortions caused by the presence of the hole. The integral method, an inverse calculation technique on which the hole drilling method is based, assumes linear elastic material behaviour and is therefore limited to the measurement of residual stresses below 60% of the yield strength. The aim of this study is to investigate the effects of elastic–plastic material behaviour on the determined non-uniform residual stress profile when the residual stresses exceed the given 60% limit. To this end, compressive residual stress profiles, as they are typically induced by laser shock peening, are investigated using finite element simulations followed by an analysis with the integral method. The obtained results from the analysis are compared to the applied residual stress profiles. An evaluation of the deviation between these two profiles provides detailed insight into the expected error as a function of hole drilling depth and the ratio of residual stress magnitude to yield strength. As an additional benefit of the presented approach, it also provides an indication of the range of depth at which the non-uniform residual stress profile should be corrected to reduce measurement error.